Comparison of Pulsed Radiofrequency, Oxygen-Ozone Therapy and Epidural Steroid Injections for the Treatment of Chronic Unilateral Radicular Syndrome - Ryska, Pavel; Jandura, Jiri; Hoffmann, Petr; Dvorak, Petr; Klimova, Blanka; Valis, Martin; Vajda, Milan (Medicina (Kaunas, Lithuania), 2021)
Background and objectives: For the treatment of chronic unilateral radicular syndrome, there are various methods including three minimally invasive computed tomography (CT)-guided methods, namely, pulsed radiofrequency (PRF), transforaminal oxygen ozone therapy (TFOOT), and transforaminal epidural steroid injection (TFESI). Despite this, it is still unclear which of these methods is the best in terms of pain reduction and disability improvement. Therefore, the purpose of this study was to evaluate the short and long-term effectiveness of these methods by measuring pain relief using the visual analogue scale (VAS) and improvement in disability (per the Oswestry disability index (ODI)) in patients with chronic unilateral radicular syndrome at L5 or S1 that do not respond to conservative treatment. Materials and Methods: After screening 692 patients, we enrolled 178 subjects, each of whom underwent one of the above CT-guided procedures. The PRF settings were as follows: pulse width = 20 ms, f = 2 Hz, U = 45 V, Z ˂ 500 Ω, and interval = 2 × 120 s. For TFOOT, an injection of 4-5 mL of an O2-O3 mixture (24 μg/mL) was administered. For the TFESI, 1 mL of a corticosteroid (betamethasone dipropionate), 3 mL of an anaesthetic (bupivacaine hydrochloride), and a 0.5 mL mixture of a non-ionic contrast agent (Iomeron 300) were administered. Pain intensity was assessed with a questionnaire. Results: The data from 178 patients (PRF, n = 57; TFOOT, n = 69; TFESI, n = 52) who submitted correctly completed questionnaires in the third month of the follow-up period were used for statistical analysis. The median pre-treatment visual analogue scale (VAS) score in all groups was six points. Immediately after treatment, the largest decrease in the median VAS score was observed in the TFESI group, with a score of 3.5 points (a decrease of 41.7%). In the PRF and TFOOT groups, the median VAS score decreased to 4 and 5 points (decreases of 33% and 16.7%, respectively). The difference in the early (immediately after) post-treatment VAS score between the TFESI and TFOOT groups was statistically significant (p = 0.0152). At the third and sixth months after treatment, the median VAS score was five points in all groups, without a statistically significant difference (p > 0.05). Additionally, there were no significant differences in the Oswestry disability index (ODI) values among the groups at any of the follow-up visits. Finally, there were no significant effects of age or body mass index (BMI) on both treatment outcomes (maximum absolute value of Spearman's rank correlation coefficient = 0.193). Conclusions: Although the three methods are equally efficient in reducing pain over the entire follow-up, we observed that TFESI (a corticosteroid with a local anaesthetic) proved to be the most effective method for early post-treatment pain relief.
Keywords: Pulsed Radiofrequency Treatment; low back pain; Humans; Radiculopathy; lidé; radikulopatie; epidural injections; Injections, Epidural; Ozone; ozone; injekce epidurální; Oxygen; pulsní radiofrekvenční terapie; pulsed radiofrequency treatment; Treatment Outcome; kyslík; výsledek terapie; ozon